PENGARUH APLIKASI PUPUK ANORGANIK MAJEMUK TERHADAP PRODUKSI TANAMAN BAWANG MERAH (Allium cepa) DAN SIFAT KIMIA TANAH - Aura Hanita Salsabila; Kurniawan Sigit Wicaksono; Syahrul Kurniawan; Novalia Kusumarini (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Onion has become one of the popular horticulture commodities in Indonesia due to the crop having several benefits. Consequently, the demand for onions in Indonesia increases annually. In contrast, the supply of onion fluctuates because of unstable onion production. One of the factors that affect unstable onion production is soil fertility degradation. Therefore, the study aimed to analyze the effect of different doses of inorganic fertilizer compounds on the chemical properties of soil, plant growth and production. The field research was conducted in the experimental land of the Faculty of Agriculture, Brawijaya University, located in Jatimulyo Village, Lowokwaru District, Malang City. This study could not detect a significant difference in fertilization doses on onion plant growth but could increase the yield and tiller numbers. The highest values of tillers number, tuber fresh weight and tuber dry weight were observed for the treatment of 50% basal fertilizer + 150% compound inorganic fertilizer and the lowest production of biomass, tillers number, wet weight, and tuber dry weight was on treatment control.